Impact of V9302, a Competitive Antagonist of Transmembrane Glutamine Flux on Reversal of Resistance in Breast Cancer Cell Lines - Nikoletta Szemerédi; Zsuzsanna Schelz; Dária Antónia Horvath; Bálint Rácz; András G. Szatmári; Hiba F. Muddather; Noémi Bózsity; István Zupkó; Gabriella Spengler (MDPI AG, 2024)
Chemotherapy is a known treatment modality that improves the long-term survival of breast cancer patients. However, due to the resistance to numerous anticancer drugs, alternative chemotherapeutic strategies are required. Regarding antimetabolic drugs, several compounds have proven anticancer properties, such as statins. The present study aimed to investigate the in vitro effects of V9302, a competitive antagonist of glutamine flux, on different subtypes of breast cancers (estrogen, progesterone, and HER2 receptor-positive or negative, and Pgp-negative and Pgp-overexpressing). The interactions of V9302 with standard chemotherapeutic drugs (doxorubicin and cisplatin) were also determined by MTT staining on breast cancer cell lines. Furthermore, the influence of V9302 on the cell cycle of MCF-7 and its Pgp-overexpressing counterpart KCR was monitored by flow cytometry. It was shown that V9302 exerted synergistic interactions with doxorubicin in all breast cancer cell lines. In cell cycle analysis, the KCR cell line was more sensitive to V9302. After 48 h, cell proliferation was completely blocked, and elevated G1, suppressed S, and decreased G2/M could be detected. Inhibition of glutamate transport can be assumed to block resistance related to Pgp.